Point prevalence survey of antibiotics usage in a tertiary care public sector hospital employing WHO methodology. - Tahir Virk, Sana; Akhtar, Nasim; Virk, Kazim Abbas; Zafar, Abeer; Zia, Zawwar; Haider, Wajeh (Infectious Diseases Journal of Pakistan, 2024)
Background: Antimicrobial resistance (AMR) kills 7 million people annually. WHO recognized AMR as a global threat in 2017 and launched the Point Prevalence Survey (PPS) methodology in 2018. The situation in Pakistan is even worse with an overall prevalence of antibiotic usage of 75 per 100 population. Material and Methods: This cross-sectional survey was conducted on a single day, 25th May 2024, at the Pakistan Institution of Medical Sciences (PIMS), with a sample size of 271 of 822 eligible patients. The PPS team collected the data using a questionnaire based on the WHO PPS methodology. All acute care and ward patients hospitalized at or before 8:00 A.m. were included. Results: A total of 271 patients were included in the survey, 110 (40.60%) were females, and 161 (59.40%) were males. The patients aged> 2 months were 248 (91.50%) and < 2 months were 23 (8.5%). The prevalence of antibiotic use in PIMS was 210 (77.6%). The culture sample sent before the first dose of antibiotic was only in 57 (27.1%) patients. The largest indication was community-acquired infections 40 (55.56%). Blood was the most common form of sample sent 45 (47.36%). The culture positivity rate was 21.05%. Klebsiella Pneumoniae was the most detected organism at 25% followed by Pseudomonas aeruginosa at 15%. The target antibiotic prescriptions were only 13.3%. Ninety percent of the antibiotics were given via parenteral route. Ceftriaxone was the most popular antibiotic used 62(20%). Conclusion: Antibiotics are widely used in our hospital, with the majority being empirical. Most antibiotics are used to treat community-acquired illnesses. Patients whose cultures were sent before their initial antibiotic treatment make up a minor proportion. Keywords: Community-acquired infections, Indication, Culture, Antibiotic consumption, Point prevalence survey, MDROs